Wpływ aktywności ruchowej i sportu na rozwój psychomotoryczny dziecka niepełnosprawnego ruchowo = The influence of physical activity and sport in the psychomotor development of physically disabled child - Anna Mędrak; Joanna Piętak; Tomasz Łosień (Kazimierz Wielki University, 2016)
Mędrak Anna, Piętak Joanna, Łosień Tomasz. Wpływ aktywności ruchowej i sportu na rozwój psychomotoryczny dziecka niepełnosprawnego ruchowo = The influence of physical activity and sport in the psychomotor development of physically disabled child. Journal of Education, Health and Sport. 2016;6(7):123-129. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57282 http://ojs.ukw.edu.pl/index.php/johs/article/view/3661       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016.     Wpływ aktywności ruchowej i sportu na rozwój psychomotoryczny dziecka niepełnosprawnego ruchowo The influence of physical activity and sport in the psychomotor development of physically disabled child   Anna Mędrak, Joanna Piętak, Tomasz Łosień   Koło Naukowe Neurorehabilitacji przy Zakładzie Rehabilitacji Leczniczej Katedry Fizjoterapii Śląskiego Uniwersytetu Medycznego w Katowicach     Streszczenie Wstęp: Sport odgrywa ważną rolę w procesie rehabilitacji dzieci niepełnosprawnych ruchowo oraz wpływa na poprawę jakości ich życia. Aktywność fizyczna poprzez swoją kompleksowość oddziałuje nie tylko na motorykę dziecka oraz funkcji życiowych, ale także uczy dyscypliny, pracy w grupie i rozwija poczucie własnej wartości  w społeczeństwie. Dobór form aktywności fizycznej zależy od stanu fizycznego i psychicznego dziecka, które są źródłem pozytywnych doświadczeń  procentujących w każdym aspekcie jego życia. Cel pracy: Celem pracy była analiza czynników mających wpływ na rozwój psychomotoryczny dzieci niepełnosprawnych ruchowo. Postawiono następujące pytania badawcze: • Jakie jest oddziaływanie sportu na rozwój psychomotoryczny dziecka niepełnosprawnego ruchowo? • Czy istnieją formy dofinansowania wsparcia rozwoju sportowego dla dzieci z niepełnosprawnością ruchową? • Jaka jest dostępność obiektów sportowych dla dzieci niepełnosprawnych ruchowo (bariery architektoniczne)?   Sport oddziałując wszechstronnie pozwala niepełnosprawnemu dziecku na akceptację własnej niepełnosprawności, uczy jak  sobie z nią radzić, jak pokonywać trudności, oraz jak poprawić formę psychiczną poprzez działanie w grupie.  Aktywność ruchowa sprzyja nawiązywaniu relacji międzyludzkich oraz pokonywaniu własnych słabości, co wspomaga proces kompleksowej rehabilitacji. Obecnie w Polsce jest coraz większa baza obiektów sportowych dostosowanych do potrzeb dzieci niepełnosprawnych ruchowo. Główne dofinansowanie pozyskiwane jest ze środków Unii Europejskiej oraz Ministerstwa Sportu i Turystyki. Istnieje także wiele fundacji wspierających rozwój sportowy dzieci niepełnosprawnych. Współcześnie coraz więcej obiektów sportowych dostosowanych jest do osób niepełnosprawnych, umożliwiając im aktywny udział w życiu społecznym i sportowym. W tym celu wykorzystuje się udogodnienia techniczne, takie jak: platformy, schodołazy, windy, krzesełka schodowe, podjazdy. W pracy podjęto próbę charakterystyki i usystematyzowania wyżej wymienionych zagadnień w odniesieniu do krajowych, ogólnodostępnych warunków  rehabilitacji dzieci niepełnosprawnych ruchowo.   Słowa klucze: dzieci, niepełnosprawność, obiekty sportowe, sport.     Introduction: Sport plays an important role in the rehabilitation of children with physical disabilities and impacts on the quality of their lives. Physical activity by its complexity not only affects the child's motor skills and life functions, but also teaches discipline, teamwork and develops self-esteem in society. The choice of physical activities depends on the physical and mental condition of the child, which are a source of positive experience which has a positive impact on every aspect of his or her life. The purpose: The aim of the study was to analyze factors influencing the psychomotor development of children with physical disabilities. The following research questions were raised: 1. What is the impact of sport on psychomotor development physically disabled child? 2. Are there any forms of financing to support the development of sports for children with physical disabilities? 3. What is the availability of sports facilities for children with physical disabilities (the architectural barriers)? By its' versatility sport allows disabled child to accept their disability, teaches how to deal with it, how to overcome difficulties and how to improve mental condition through the action of the group. Physical activity promotes networking and overcoming their own weaknesses, which supports the process of comprehensive rehabilitation. Poland currently has a growing base of sports facilities adjusted to the needs of children with physical disabilities. Majority of funds is sourced from the European Union and the Ministry of Sport and Tourism. There are also many foundations supporting athletic development of children with disabilities. Nowadays, more and more sport facilities are being adapted to people with disabilities, allowing them to actively participate in social life and sport. The technical facilities, such as platforms, stair elevators, stair chairs, driveways are used to adjust architecture to disabled's needs. This paper is an attempt to characterize and systematize the issues mentioned above  in relation to conditions of national, public program of rehabilitation of children with physical disabilities.   Key words: children, disabilities, sports facilities, sports.